Substantiation of optimal parameters of rapeseed cake extrusion process - Torebek Bаib`atyrov; Saule Zhienbayeva; Altynai Abuova; Askhat Umbetbekov; Mahamedkali Kenzhekhodzhaev; Zhamilya Mazhit; Zhazira Mukazhanova; Shynar Sanyazova (Caspian Journal of Environmental Sciences)
The inclusion of rapeseed products in animal and poultry feeds is hindered by the presence of low-nutrient compounds like erucic acid, glucosinolates, tannins, and phytic acid, which can be harmful and reduce overall productivity. This study investigates the variability of glucosinolate content in rapeseed due to growing conditions and evaluates the impact of replacing traditional meals with rapeseed meal in animal feeds. Despite mixed results, the research highlights the potential of double-zero varieties of rapeseed and turnip rape oil in the food and feed industry. The study emphasizes the necessity of removing weed impurities and reducing fiber content to obtain high-quality rapeseed meal. Various processing methods, particularly extrusion, have been explored to enhance digestibility and reduce harmful substances. The findings demonstrate that extrusion effectively decreases glucosinolate and erucic acid content, while maintaining protein levels, making rapeseed meal a promising and cost-effective alternative to soybean and sunflower meals for broiler chicken feed.